Religious Dialectics: The Debate Between Persis and The Ahmadiyya Qadiani During The Dutch Colonial Period, 1925–1939 - Rabbani, Sunalar Sam; Hakim, Sudarnoto Abdul (Green Publisher Indonesia, 2026)
Ahmadiyya, a transnational movement founded by Mirza Ghulam Ahmad in late 19th-century India, entered Indonesia during the national movement era and, despite gaining limited sympathy, faced strong rejection from mainstream Islamic organizations for its controversial teachings, especially his prophetic claims. This research aims to examine the religious dialectics between the Ahmadiyya Qadian and the Islamic Union (PERSIS) in 1925–1939, with a focus on attitudes and responses This research uses historical methods combined with the social approach and analysis of the theory of charismatic authority from Max Weber to understand the appeal of Mirza Ghulam Ahmad's leadership and the forms of delegitimization carried out by his opponents. The results of the study show that the polemic between Ahmadiyya and PERSIS is not only a theological conflict, but also part of the discourse contestation to determine Islamic orthodoxy in Indonesia. Da'wah media such as magazines and books are important tools in shaping public opinion and spreading ideological arguments. This polemic of the debate reflects the process of constructing religious identity in the midst of colonialism, as well as the efforts of local Islamic organizations in building valid religious authority in the midst of Islamic renewal and transnational ideological challenges such as Ahmadiyah.